Linkage analysis of families with severe childhood autosomal recessive muscular dystrophy in Morocco indicates genetic homogeneity of the disease in north Africa. Issue 4 (April 1994) - el Kerch, F; Sefiani, A; Azibi, K; Boutaleb, N; Yahyaoui, M; Bentahila, A; Vinet, M C; Leturcq, F; Bachner, L; Beckmann, J
Abstract : It has been previously shown in Tunisian and Algerian families that the locus for SCARMD maps to the proximal part of 13q, and in Algerian families that the disease is associated with deficiency of the 50 kDa dystrophin associated glycoprotein (50DAG). We have tested this linkage in six families from Morocco where this disease is also prevalent. In one family the 50DAG was tested and found to be negative in a muscle biopsy. Our results showed similar linkage in this country, with statistical tests indicating genetic homogeneity between the three Maghreb countries.